2022
DOI: 10.3390/su141711064
|View full text |Cite
|
Sign up to set email alerts
|

A Human Growth Perspective on Sustainable HRM Practices, Worker Well-Being and Organizational Performance

Abstract: Care services pose new challenges and opportunities for the implementation of sustainable HRM practices related to worker involvement and well-being because of their relational nature. The article is framed in terms of the job demands and resources model and discusses the impact of sustainable HRM (SHRM) practices on organizational performance in terms of service quality and organizational innovation in social and care services. A possible mediating role of immaterial satisfaction between SHRM and performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 133 publications
1
44
0
1
Order By: Relevance
“…Jerónimo et al (2020) developed a very interesting study showing that the relation between SHRM and employee performance is not a direct one and is mediated by either perceived organizational rationale for sustainability or organizational identification. Furthermore, Tortia et al (2022) found compelling results showing that SHRM practices related to involvement and workload positively influence performance. In a similar way, Manzoor et al (2019) found that sustainable HRM practices, such as selection, participation, and employee empowerment, have a significant and positive influence on employee job performance.…”
Section: Organizational Attractiveness Performance and Turnover Inten...mentioning
confidence: 99%
“…Jerónimo et al (2020) developed a very interesting study showing that the relation between SHRM and employee performance is not a direct one and is mediated by either perceived organizational rationale for sustainability or organizational identification. Furthermore, Tortia et al (2022) found compelling results showing that SHRM practices related to involvement and workload positively influence performance. In a similar way, Manzoor et al (2019) found that sustainable HRM practices, such as selection, participation, and employee empowerment, have a significant and positive influence on employee job performance.…”
Section: Organizational Attractiveness Performance and Turnover Inten...mentioning
confidence: 99%
“…Nitekim literatürde, diğerlerinin yanı sıra sosyal açıdan sorumlu insan kaynakları yönetimi, yeşil insan kaynakları yönetimi gibi kavramlarla da anılmaktadır (Proença;2022,2). Sürdürülebilir insan kaynakları yönetiminin tanıma baktığımızda, kurumsal sürdürülebilirlik, sosyal sorumluluk, sürdürülebilir çalışma sistemlerine odaklanan çeşitli disiplinlerin ve araştırma alanlarının sonucu olarak ifade edilebilir (Davidescu;2020;2) Bir diğer tanıma göre insan kaynaklarının kullanımında uzun vadeli sürdürülebilirliği sağlamak için insan kaynakları yönetimi uygulamalarının tasarımında ekonomik, finansal ve sosyal unsurların ortak arayışını birleştiren bir kavramdır (Tortia;2022,1).…”
Section: Sürdürülebi̇li̇r İkyunclassified
“…The importance of employee commitment has increased due to organizations' need to control the current employee image. By clearly articulating an employee's distinctive qualities and the associated employment value proposition, employee work attitude practices help make employees more appealing to possible qualified candidates in particular (Tortia et al, 2022). At this moment, employee work attitude practices are crucial for the retention of current personnel, successful stakeholder reward, and corporate selection (Shiferaw, 2022).…”
Section: Introductionmentioning
confidence: 99%